Phenotypic evolution of appearance quality and cooking and taste quality of hybrid rice over the past 40 years in China - Fan, Jiongjiong; Li, Wei; Bian, Ying; Zhang, Zhengjiu; Yang, Ruoju; Xu, Xia; Cheng, Benyi; Yang, Shihua; Wu, Jianli; Zhang, Xiaobo; Gong, Junyi (Frontiers in Plant Science, 2024)
Since the inception of hybrid rice technology 50 years ago, it has not only substantially increased rice yield per unit area but also expedited the development of high-quality rice varieties. However, the evolutionary characteristics of hybrid rice quality remain unclear. To address this gap, it is imperative to leverage more representative and comprehensive hybrid rice resources to analyze phenotypic variation diversity and its primary genetic basis, thereby offering more efficient guidance for molecular breeding. In this study, we selected 2,618 hybrid rice varieties that have been nationally or provincially approved in China over the past 40 years. We analyzed the ecological and chronological evolution characteristics of eight rice quality-related traits: grain length, grain width, grain length-width ratio, chalky grain ratio, chalkiness degree, alkali spreading value, gel consistency, and amylose content (AC). Additionally, we utilized the 'Rice-Navi' system to evaluate the primary molecular basis underlying this evolution. The results revealed that among the eight traits, the coefficient of variation for chalkiness degree was the highest at 0.88, whereas the lowest value of 0.07 was observed for grain width. Significant correlations were found among these traits. The phenotypic evolution results for six major ecological types-Early-season cultivation of indica in South China, Late-season cultivation of indica in South China, Mid-season cultivation of indica in the upper reaches of the Yangtze River, Early-season cultivation of indica in the middle and lower reaches of the Yangtze River, Mid-season cultivation of indica in the middle and lower reaches of the Yangtze River, and Late-season cultivation of indica in the middle and lower reaches of the Yangtze River-indicated that, except for E4, the quality of rice in the other five major ecological types exhibited a significant chronological improvement trend. This trend was highly correlated with the utilization of major superior alleles. Concurrently, the primary genetic background of hybrid rice quality displayed certain ecological diversity characteristics. Overall, this study elucidated the evolutionary characteristics of appearance quality and cooking and taste quality of hybrid rice in southern China from both ecological and chronological perspectives, providing valuable data support for the efficient molecular improvement of rice quality.